Mental health services in Nepal: Is it too late? - Simkhada, P; van Teijlingen, E; Marahatta, SB (Journal of Manmohan Memorial Institute of Health Sciences, 2015)
No Abstract DOI: http://dx.doi.org/10.3126/jmmihs.v1i4.12012 Journal of Manmohan Memorial Institute of Health Sciences Vol. 1, Issue 4, 2015: 1-2